Pengaruh Relaksasi Diafragma, Relaksasi Otot Progresif dan Relaksasi Nafas terhadap Penurunan Rasa Cemas pada Ibu Hamil Trimester III - Yuli Mulyati; Astrid Novita; Nurwita Trisna (MPI Press, 2021)
Introduction: The stress of a pregnant woman that comes from within is related to feeling anxious about her ability to adapt to her pregnancy conditions. Feelings of anxiety and worry in the third trimester, are increasingly getting into the gestational age of seven months and over and before delivery. Objectives: The purpose of this study was to determine the effect of diaphragm relaxation, progressive muscle relaxation, and breath relaxation on reducing anxiety in third trimester pregnant women at BPM Mira Laura, Bogor City. Method: This study used a quasi-experimental research method (Quasi Experiment) and used a non-randomized control group pre-test-post-test design approach, with a sampling technique namely quota sampling with a sample size of 45 respondents. The research instrument was the Speilberg State-Trait Anxiety Inventory (STAI) questionnaire. The data were processed using SPSS. Result: The result of the Paired T-Test is an effect of diaphragm relaxation (P=0,000; OR=2.883), progressive muscle relaxation (P=0,000; OR=4.579), and breath relaxation (P=0,000; OR=4.655) on reducing anxiety in third trimester pregnant women at BPM Mira Laura, Bogor City. Conclusion: With this research, it is hoped that health workers, especially midwives, can provide midwifery care to pregnant women to reduce anxiety by doing or teaching pregnant women relaxation so that pregnant women can carry out these therapies sustainably and independently at home because it is very easy to apply.